(untitled) - Schonberger, Richard J. (New York, 1996)
Schonberger was one of those who made early note of Japanese manufacturing methods, in Japanese Manufacturing Techniques: Nine Hidden Lessons in Simplicity (1982). Now he surveys the state of manufacturing today in nine different countries. He argues that, rather than financial indicators, two key measures consistently correlate with a company's strength. One, inventory turnover, is easy to measure. The other, customer satisfaction, is not. Schonberger developed 16 principles of "customer-focused, employee-driven, data-based performance" that companies can use to "score" themselves and evaluate their ability to satisfy the customer. He uses the results of scoring done for almost 140 manufacturers to provide benchmarks for other companies and to help illustrate each of his principles. Although academically grounded, this book will be of value to practitioners who seek to improve customer satisfaction
Keywords: Industrial management.,Production management.,Manufacturing processes